Taking science education beyond schooling - Roth, Wolff-Michael (Canadian Journal of Science, Mathematics and Technology Education, 2002)
The shape and content of science education has always been articulated from the scientist's perspective. Recently, an increasing number of science educators have recognized the serious limitations of this perspective and have proposed to define scientific literacy from societal or citizenship perspectives. In this article, I argue that these alternatives will remain as limited as their predecessors unless the very structures of schooling are called into question. Furthermore, I argue that alternatives cannot be designed at the drawing board by theoreticians, but have to be grounded in praxis, thereby providing concrete trajectories along which science education can actually change.